Occurrence and Distribution of Sri Lankan Cassava Mosaic Virus in the Stems of Cassava - Anitha, Jose; S., Edison; T., Makeshkumar (JOURNAL OF ROOT CROPS, 2019)
The distribution of Sri Lankan cassava mosaic virus (SLCMV) in the buds regenerated from the nodes of stem cuttings varied with different varieties. Using different diagnostic techniques (ELISA, PCR and NASH), the SLCMV distribution in 8 varieties of cassava viz., Sree Sahya, Sree Prakash, Sree Visakham, Sree Padmanabha, Sree Vijaya, M-4, H-165 and H-226 were diagnosed. Top portions (one third of total stem used for planting) of the stems in all the varieties tested had maximum virus accumulation except Sree Padmanabha, which showed high virus accumulation in bottom portion. Similar results were obtained from the diagnosis of bark samples of all the varieties with variation in the virus accumulation level.